Beta-adrenoЬlockers in patients with chronic heart failure and chronic obstructive pulmonary disease - M. E. Statsenko; D. A. Ivanova; O. E. Sporova; S. V. Belenkova (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To compare clinical effectiveness and safety of bisoprolol and metoprolol as a part of basis chronic heart failure (CHF) therapy in patients with coexisting chronic obstructive pulmonary disease (COPD).Material and methods. The study included 60 patients at Day 25-30 after myocardial infarction, complicated by functional Class (FC) II-III CHF. All participants suffered from moderate to severe COPD. All patients underwent clinical examination, CHF FC assessment, echocardiography, 24-hour electrocardiography monitoring, renal function, lung function (LF), and quality of life assessment. The participants were randomised into two groups: group I (n=30) received bisoprolol, and Group II (n=300) - metoprolol tartrate as a part of basis CHF therapy.Results. Comparing to metoprolol, bisoprolol more effectively increased left ventricular (LV) ejection fraction, decreased diastolic dysfunction severity, and reduced LV remodelling, did not affect LF and did not increase airway resistance.Conclusion. Comparing to metoprolol tartrate, bisoprolol was more effective and safe in patients with CHF and Stage II-III COPD.